Convergence through communication and competition? The internationalization of secondary and higher education policies in Switzerland - Tonia Bieber (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2011)
Far-reaching transformations in Swiss education were pushed in the last decade by two prominent international initiatives, namely the 1999 Bologna process and the OECD's PISA study starting in 2000. To what extent and in which way were these soft governance initiatives able to trigger Swiss policy convergence towards their policy models? Drawing on convergence approaches, it is assumed that mechanisms of transnational communication and regulatory competition acted as driving forces of the Swiss reform wave in the last decade. Results show that Swiss secondary education policy exhibits a considerable level of convergence towards the OECD recommendations based on the PISA results, and that reforms in Swiss higher education highly conformed to the Bologna aims. While different communicative mechanisms furthered policy convergence in Swiss secondary and higher education towards the international models of the PISA study and the Bologna process, in both cases regulatory competition was highly effective in promoting domestic reforms. Applying qualitative methods of expert interviews and document analysis, this paper contributes to research on policy convergence. It fills the research gap concerning the role of the newly emerged, but ever more influential education-political actors of the OECD and the EU as promoters and of domestic actors as both supporters and antagonists of convergence.
Keywords: 300; Bologna process; EU; OECD; PISA study; policy convergence; Switzerland